The experiences of partners of people transitioning to a different gender : a thesis presented in fulfilment of the requirements for the degree of Masters in Science in Psychology at Massey University, Wellington, New Zealand - Chester, Krystle D (My University, 2016)
Previous research has shown that gender transition of one partner in a relationship impacts the non-transitioning partner’s sense of identity, emotional wellbeing and their relationship with their transgender partner. This topic is under-researched and very little of this research has examined the wider social implications of being a partner of a person making a gender transition. To date no published research of this kind has been conducted in New Zealand. This project explored the experiences of the former and current cisgender (non-transgender) partners of people transitioning from one gender to another. In particular the project explored how cisgender partners felt their partners’ transition impacted on them and their relationships, as well as how they experienced the disclosure of their partners’ transgender identity. Six participants (four were separated from their partners, five women, one man, aged 21 to 39 years, all identified as non-heterosexual except one) were recruited through advertising via social media and support groups. Participants took part in in-depth semi-structured one-on-one interviews; these were transcribed and analysed using interpretative phenomenological analysis (IPA). Three superordinate themes and ten subthemes were found. They were: “Coming Out as a Process”; “Support”; and “Changes to the Relationship and Self”. Many of the participants experienced their partners’ disclosure as transgender as a gradual and shared process. Participants felt that their partners’ transition shaped their relationships and themselves in different ways and responded to their partners’ transition with a range of emotions and cognitions. Participants generally felt supported by others but felt there was a lack of understanding, support and resources that were specific to their needs. There is clear need for good sources of support for cis partners. Future research efforts could usefully explore the support needs of partners of transitioning people and the best ways to distribute this support.
Keywords: Transgender people; Family relationships; Transgenderism; Psychological aspects